Critical Distance of the Seismic Waves’ Impact in Disintegration of Rock Blasting - Dušan Kudelas; Blažej Pandula; Michal Cehlár; Marcela Taušová; Ján Koščo (Shock and Vibration)
The presented paper deals with attenuation of seismic waves, which depends on the degree of disintegration of the rock environment in which seismic waves are propagated due to the explosion of explosive charges during blasting operations. Measurements of the impact of seismic waves were conducted to determine the best possible way to absorb these waves. The aim of the article is to identify the existence of a critical distance and the determination of the critical point from which the propagation of the velocity is not dependent on the type of deposit and the environment in which the seismic wave propagates. Statistical methods were used for these findings. The result is the determination of the distance of 80 m in which the speed on the individual deposits varied. From this limit on, there was no significant difference in the speed of propagation on the individual deposits.